Effects of Sparganii Rhizoma on Osteoclast Formation and Osteoblast Differentiation and on an OVX-Induced Bone Loss Model - Lee, Sungyub; Kim, Minsun; Hong, Sooyeon; Kim, Eom Ji; Kim, Jae-Hyun; Sohn, Youngjoo; Jung, Hyuk-Sang (Frontiers in Pharmacology, 2022)
Postmenopausal osteoporosis is caused by an imbalance between osteoclasts and osteoblasts and causes severe bone loss. Osteoporotic medicines are classified into bone resorption inhibitors and bone formation promoters according to the mechanism of action. Long-term use of bisphosphonate and selective estrogen receptor modulators (SERMs) can cause severe side effects in postmenopausal osteoporosis patients. Therefore, it is important to find alternative natural products that reduce osteoclast activity and increase osteoblast formation. Sparganii Rhizoma (SR) is the dried tuberous rhizome of Sparganium stoloniferum Buchanan-Hamilton and is called "samreung" in Korea. However, to date, the effect of SR on osteoclast differentiation and the ovariectomized (OVX )-induced bone loss model has not been reported. In vitro, tartrate-resistant acid phosphatase (TRAP) staining, western blots, RT-PCR and other methods were used to examine the effect of SR on osteoclast differentiation and osteoblasts. In vivo, we confirmed the effect of SR in a model of OVX-induced postmenopausal osteoporosis. SR inhibited osteoclast differentiation and decreased the expression of TNF receptor-associated factor 6 (TRAF6), nuclear factor of activated T cells 1 (NFATc1) and c-Fos pathway. In addition, SR stimulates osteoblast differentiation and increased protein expression of the bone morphogenetic protein 2 (BMP-2)/SMAD signaling pathway. Moreover, SR protected against bone loss in OVX-induced rats. Our study suggests that SR may be new alternative for the treatment of postmenopausal osteoporosis.